A novel CLCNKB mutation in a Chinese girl with classic Bartter syndrome: a case report - Binlu Zhu; Hong Jiang; Meiling Cao; Xueqi Zhao; Hongkun Jiang (BMC, 2019)
Abstract Background Bartter syndrome (BS) is a rare autosomal recessive disorder of salt reabsorption at the thick ascending limb of the Henle loop, characterized by hypokalemia, salt loss, metabolic alkalosis, hyperreninemic hyperaldosteronism with normal blood pressure. BS type III, often known as classic BS (CBS), is caused by loss-of-function mutations in CLCNKB (chloride voltage-gated channel Kb) encoding basolateral ClC-Kb. Case presentation We reported a 15-year-old CBS patient with a compound heterozygous mutation of CLCNKB gene. She first presented with vomiting, hypokalemic metabolic alkalosis at the age of 4 months, and was clinically diagnosed as CBS. Indomethacin, spironolactone and oral potassium were started from then. During follow-up, the serum electrolyte levels were generally normal, but the patient showed failure to thrive and growth hormone (GH) deficiency was diagnosed. The recombinant human GH therapy was performed, and the growth velocity was improved. When she was 14, severe proteinuria and chronic kidney disease (CKD) were developed. Renal biopsy showed focal segmental glomerulosclerosis (FSGS) with juxtaglomerular apparatus cell hyperplasia, and genetic testing revealed a point deletion of c.1696delG (p. Glu566fs) and a fragment deletion of exon 2-3 deletions in CLCNKB gene. Apart from the CBS, ostium secundum atrial septal defect (ASD) was diagnosed by echocardiography. Conclusions This is the first report of this compound heterozygous of CLCNKB gene in BS Children. Our findings contribute to a growing list of CLCNKB mutations associated with CBS. Some recessive mutations can induce CBS in combination with other mutations.